DEVELOPMENT OF ASSESSMENT INDICATORS FOR EVALUATING PERFORMANCE OF SUPPLIERS IN PT.INTI - Pratiwi, Rahmi
PT. Indonesia Telecommunications Industry (INTI) is a bona fide State-Owned Enterprise that cannot be separated from the auditor's approval. Audit is a systematic evaluation/ evaluation process for evaluating the efficiency and effectiveness of business processes carried out. At this time based on the results of the audit found results with minor findings and observations in terms of supplier ratings. Minor findings state that these criteria are not fully objective, whereas in the collection of observations announced the criteria must be reviewed again so that they are measured and translated. The instruments of assessment/ indicators for the assessment of current supplier performance that are used are not detailed, only limited to general assessment. The instrument of assessment includes aspects of delivery, quality, service, administration, security, occupational health and safety (K3), environment and finance. Based on the assessment instrument and based on the audit findings, an instrument is developed to obtain more detailed and objective indicators. Assessment instruments or indicators are effects of the dimensions discussed, so the indicators in this study reflect reflective because they want to see the relationship of elements in the indicator. The development of the model for obtaining an instrument was carried out based on the Liquiddanu reference model (2015) and the results of the allocation development using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. Weighting is generated through the Haenlein and Kaplan (2004) path model diagram in order to analyze the pattern of relationships between variables and also directly or indirectly separate the independent variables (exogenous) from the independent variable (endogenous). Based on the development of the conceptual model, one new aspect will be used to evaluate supplier performance. These aspects are aspects of after-sales aspects. The results of the development of conceptual and operational models obtained a number of three indicators, five elements, and two types of indicators consisting of five requirements indicators in the form of documents and certificates and 17 assessment indicators in the form of performance carried out by suppliers. The three dimensions of assessment produced include aspects of quality, delivery, and after-sales. The six assessment elements produced include quality of goods, quality management, delivery reliability, administrative response, and service. 17 indicators are divided into three dimensions of assessment, namely eight indicators on aspects of quality, five indicators on aspects of delivery, and four indicators on aspects of after-sales. The biggest weight on the dimension of assessment was obtained from aspects of after sale aspects (47.61%), delivery aspects (27.71%) and quality aspects (24.68%). The five biggest indicator weights are maintenance and repair services (12.02%), responsive services to resolve customer complaints (12.02%), transportation handling services (11.98%), goods warranty services (11.58%), and document delivery accuracy (6.11%).